The Role of Language in Identity Formation: A Linguistic Perspective in Education - David Darwin; Evizariza Evizariza (PT. Anagata Sembagi Education, 2024)
Language plays an important role in the formation of individual and group identities in educational settings. This research aims to understand how language influences student identity from cultural, social, academic and digital perspectives. Using a qualitative approach and case study design, data was collected through in-depth interviews, participatory observation and document analysis. The research subjects included 30 informants from three schools with diverse cultural and social backgrounds. The results show that local languages strengthen students' cultural identity, despite being pressured by the dominance of national and foreign languages due to globalization. In the social context, language functions as a tool for status negotiation and group dynamics. Teaching foreign languages, such as English, increases students' global competence but risks reducing appreciation for local languages. In the digital age, language use on social media reflects students' creative identities but often clashes with formal language norms in schools. This research emphasizes the importance of a balanced language education policy to support global language acquisition while preserving local languages. With this approach, education can help students build an inclusive identity, integrate local values in a global context, and strengthen their cultural connections holistically.